Death penalty and the victims - Simonovic, Ivan (United Nations, Human Rights Office of the High Commissioner, 2016)
"This publication includes perspectives from a broad range of victims. While some of them are family members of crime victims, others are victims of human rights violations in application of the death penalty, of its brutality and traumatic effects"--Back cove